Blood Cultures in Ambulatory Patients Who Are Discharged from Emergency with Community-Acquired Pneumonia - Thomas J Marrie (Canadian Journal of Infectious Diseases)
OBJECTIVES: To determine the factors that predict whether or not ambulatory patients with community-acquired pneumonia (CAP) treated in an emergency room (ER) setting will have blood cultures drawn and the factors that predict a positive blood culture.